2017
DOI: 10.1111/dewb.12163
|View full text |Cite
|
Sign up to set email alerts
|

‘We are the eyes and ears of researchers and community’: Understanding the role of community advisory groups in representing researchers and communities in Malawi

Abstract: Community engagement to protect and empower participating individuals and communities is an ethical requirement in research. There is however limited evidence on effectiveness or relevance of some of the approaches used to improve ethical practice. We conducted a study to understand the rationale, relevance and benefits of community engagement in health research. This paper draws from this wider study and focuses on factors that shaped Community Advisory Group (CAG) members’ selection processes and functions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 35 publications
(63 citation statements)
references
References 2 publications
1
62
0
Order By: Relevance
“…This exercise helped to improve community understanding of study information before giving consent [ 24 ]. Ethical issues pertaining to community engagement have however been widely discussed particularly in the literature on Community Advisory Boards (CABs) [ 25 – 29 ]. Nevertheless, successful examples of engaging CABs to enhance ethical conduct of research have been reported in cases where CABs have been properly set up, they understand their advisory roles and they have the ability to analyze and communicate ethical issues [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This exercise helped to improve community understanding of study information before giving consent [ 24 ]. Ethical issues pertaining to community engagement have however been widely discussed particularly in the literature on Community Advisory Boards (CABs) [ 25 – 29 ]. Nevertheless, successful examples of engaging CABs to enhance ethical conduct of research have been reported in cases where CABs have been properly set up, they understand their advisory roles and they have the ability to analyze and communicate ethical issues [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, several studies have reported challenges in engaging community members as collaborative partners through community advisory boards (CABs) or community advisory groups (CAGs). These studies have reported conflicting roles of CABs, which are asked to provide input to protocol development and minimize harm but also to advance research goals by facilitating participant recruitment 12 14 . Other challenges include limited understanding of health research and monetary expectations among CAB members, dependence on researchers for finances, and lack of authority to influence decisions concerning research 15 18 .…”
Section: Introductionmentioning
confidence: 99%
“…CAB activities included training sessions, periodic meetings, focus group discussions, site visits, conference calls, and group emails. Ten articles described training sessions for CAB members, including technical medical expertise trainings, CAB and community leadership skills improvement sessions, protocol specific training, report writing guidance, and protection of research participants, which typically lasted several days and were uniformly conducted before CABs began operating in their advisory capacity [13, 18, 26, 33]. Most CAB members had no formal medical or public health training, and consequently organizing teams (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Most CAB members had no formal medical or public health training, and consequently organizing teams (e.g. research teams, staff from professional training institutions, and universities) tended to focus training on improving members’ medical knowledge as well as addressing research goals and ethics [13, 18, 33, 38, 45, 48, 49]. Once formed, most CABs held periodic meetings, with meeting frequently ranging from weekly to monthly to quarterly to yearly.…”
Section: Resultsmentioning
confidence: 99%